A 150-Year Conundrum: Cranial Robusticity and Its Bearing on the Origin of Aboriginal Australians. (22nd December 2010) - Curnoe, Darren
Abstract : The origin of Aboriginal Australians has been a central question of palaeoanthropology since its inception during the 19th Century. Moreover, the idea that Australians could trace their ancestry to a non-modern Pleistocene population such as Homo erectus in Southeast Asia have existed for more than 100 years, being explicitly linked to cranial robusticity. It is argued here that in order to resolve this issue a new program of research should be embraced, one aiming to test the full range of alternative explanations for robust morphology. Recent developments in the morphological sciences, especially relating to the ontogeny of the cranium indicate that character atomisation, an approach underpinning phylogenetic reconstruction, is fraught with difficulties. This leads to the conclusion that phylogenetic-based explanations for robusticity should be reconsidered and a more parsimonious approach to explaining Aboriginal Australian origins taken. One that takes proper account of the complex processes involved in the growth of the human cranium rather than just assuming natural selection to explain every subtle variation seen in past populations. In doing so, the null hypothesis that robusticity might result from phenotypic plasticity alone cannot be rejected, a position at odds with both reticulate and deep-time continuity models of Australian origins.